Implementation of Cloud Computing Data Security Based on Hybrid Elliptical Curve Cryptography - Krishnamoorthy, N.; Umarani, S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The adoption of cloud storage has increased in a rapid pace across all kinds of applications. Though cloud storage has been used frequently, there are two key worries the consumer has when using the cloud storage. Recently, the storage and retrieval of data in the cloud architecture is an attractive research field in cloud computing. Besides those, economical resource use and secure data transfer are additional limits over the numerous internet services. The rise of cryptographic encryption and decoding technologies assure the privacy protection of cloud uploaded data. An important activity prior to an encryption mechanism is to understand the levels of security, storage and data access risks. Cloud computing, a globalized platform to allow the virtual execution of process lead to outsourcing of numerous services such as data processing, remote execution and storage to cloud servers. This work comprises several sequential procedures including key evaluation mechanism, production of key derivation policies with two stages namely, master key generation and private key generation and key verification. The key assessment mechanism reveals that the inclusion of attributes of data and data owner decides the execution of both encryption and decryption. Hybrid Elliptical Curve Cryptography (HECC) to bring security into Web Application based cloud services while providing security for hybrid cloud networks and the data they store and retrieve from the clouds. The proposed security frameworks have been implemented and also compared the effectiveness of the system with the existing models in terms of encryption and computational burden along with the security level when storing, retrieving and accessing the data in cloud environment.